The Educational Actions in Art Museums the Brazil (Palíndromo, 2013)
This article reports the main educational activities developed today in Art Museums in Brazil. The identification of such actions occurred from literature review and the visit about fifty Museums, Cultural Center, Institutes, Galleries and Memorials. Note that the actions identified generally are offered by major museological institutions and do not represent the reality of art museums in Brazil.
Keywords: Education Actions; Museum; Art/education